MARANTACEAE IN SULAWESI - M. ARDIYANI; A. D. POULSEN; P. SUKSATHAN; F. BORCHSENIUS (BRIN Publishing (Penerbit BRIN), 2010)
ARDIYANI, M., POULSEN, A. D., SUKSATHAN, P., BORCHSENIUS, F. 2010. Marantaceae in Sulawesi. Reinwardtia 13(2): 213-220. - Six species of Marantaceae occur in Sulawesi. We present a key to the species together with a taxonomic treatment with notes on species delimitation, distribution, habitat and ecology, vernacular names and uses. One species endemic to Sulawesi and not covered by any contemporary publication, Phrynium longispicum (Warb. ex K. Schum.) Suksathan & Borchs. is described and neotypified. Donax canniformis (G. Forst.) K. Schum., Phrynium pubinerve Blume, Phrynium robinsonii (Valeton) Suksathan & Borchs, Stachyphrynium latifolium (Blume) K. Schum. and Stachyphrynium repens (Korn.) Suksathan & Borchs. are also reported from Sulawesi and characterized. For the two last species these occurrences represents an extension of their previously known range across Wallace's line.